The Book of Judith: from a symbolic story to a historical mystery - MIKHAILOVA, Tatiana (Historia i Świat, 2018)
The Apocryphal tale of Judith describes the story of the encounter between the Assyrians and the Jews, who managed to overcome the enemy through the faith and strength of Judith. The Book is rich in historical and geographical details but the general historical stage is false or more likely intentionally modified. The reason of this modification may be the creation of a pseudo-historical reality with the purpose to make an impression of a timeless lesson. But with the course of time this symbolic role of this artistical device is slackening so that the process of decoding advances to the forefront